Vloga pripadnikov slovenskih avtohtonih manjšin v sosednjih državah in slovenskih izseljencev v osamosvajanju Slovenije - Klemenčič, Matjaž (Annales. Series historia et sociologia, 2017)
The author attempts to answer the question to what extent the activities of the Slovenians in neighboring countries and Slovenian emigrants contributed to their new home countries recognitions of the independence. On the basis of original archival sources, newspaper articles and available literature it was confirmed that the international community at the crossroads of the 1990s, did not favor the emergence of new nation-states. The Slovenians living outside the Republic of Slovenia were at that time practically the only ones on which the Slovenians from Slovenia in those crucial moments could rely. As a result, Slovenian politicians then asked the representatives of the Slovenian minorities and Slovenian emigrants for the support and co-operation in all important steps. These were the key moments in their efforts to infl uence the policy in the new home countries to recognize the independence of Slovenia. Members of indigenous Slovenian minorities in neighboring countries and Slovenian immigrants of all generations then showed a lot of interest in Slovenia and a high degree of unity in seeking the recognition of Slovenian independence by their new homelands. Although the international recognition of Slovenia was primary not the result of their pressure on the governments of the countries of their settlement, it is necessary to recognize the achievements of these communities that affected the policies of their countries towards Slovenia.
Keywords: binternational community; history; independence; international recognition; mednarodna skupnost; mednarodno priznanje; narodne manjšine; osamosvojitev; Slovene emigrants; Slovene history; Slovenia; Slovenian indigenous minorities; Slovenija; slovensko izseljenstvo; zgodovina